NEW AND RARE FOR THE REPUBLIC OF KARELIA SPECIES OF APHYLLOPHOROID FUNGI (BASIDIOMYCOTA). III - Anna Ruokolainen; Vera Kotkova (Proceedings of the Karelian Research Centre of the Russian Academy of Sciences, 2017)
Three species of aphyllophoroid fungi (Clavulicium macounii (Burt) Parmasto, Tomentella fuscocinerea (Pers.) Donk, Xenasma rimicola (P. Karst.) Donk) were for the first time recorded from the Republic of Karelia. Xenasma rimicola was a new finding for North-West Russia. Also, new data are presented on the distribution of 15 species (11 are new for Kon and 4 are new for Kton). 13 species were recorded for the first time for the Kivach Strict Nature Reserve, including Asterostroma laxum which is listed in the Red Data Book of the Republic of Karelia (2007). Four species are new for Vodlozersky National Park. Data on localities, habitats and substrates of all these species are provided. The specimens are kept in the herbaria of the Forest Research Institute of the Karelian Research Centre RAS (PTZ) and Komarov Botanical Institute RAS (LE). The new findings have expanded our knowledge of the distribution of aphyllophoroid fungi in the republic.